Enolase1 overexpression regulates the growth of gastric cancer cells and predicts poor survival. Issue 11 (19th June 2019) - Qiao, Hui; Wang, Yufeng; Zhu, Bingdong; Jiang, Lei; Yuan, Wenzhen; Zhou, Yongning; Guan, Quanlin
Abstract: Gastric cancer has become the third most common cancer around the world. In patients with gastric cancer, the 5‐year survival rate is still low. However, the mechanism underlying gastric cancer remains largely unknown. As a glycolytic enzyme, enolase 1 (ENO1) is widely expressed in most tissues. The functions of ENO1 have been reported in various types of cancer. Here in this study, we identified that ENO1 promoted the growth of gastric cancer cells through diverse mechanisms. Our immunohistochemical, bioinformatic and Western blot data showed that ENO1 was significantly overexpressed in human gastric cancer cell lines and tissues. The survival analysis revealed that ENO1 overexpression predicted poor survival in the patients suffering gastric cancer. Knockdown of ENO1 expression repressed the rate of proliferation and capacity of colony formation in two human gastric cancer cell lines (MGC‐803 and MKN‐45). In addition, knockdown of the expression of ENO1 led to the arrest of the cell cycle at the G1 phase and promoted the apoptosis of MKN‐45 and MGC‐803 cells. The further microarray and bioinformatic analysis revealed that ENO1 regulated the expression of diverse genes, many of which are involved in the progress of cancer. Taken together, our data demonstrated that ENO1 was an oncogene‐like factor and might serve as a promising target for the treatment of human gastric cancer. Abstract : Enolase 1 (ENO1) is overexpressed in gastric cancer cells and predicts poor survival; ENO1 knockdown suppresses the growth of gastric cancer cells.